Agricultural credit rationing in Ghana: what do formal lenders look for?. Issue 3 (26th August 2014) - Awunyo-Vitor, Dadson; Mahama Al-Hassan, Ramatu; Bruce Sarpong, Daniel; Egyir, Irene
Abstract : Purpose: – The purpose of this paper is to investigate the determinants of agricultural credit rationing by formal lenders in Ghana. Design/methodology/approach: – This study employed descriptive statistics, analysis of variance (ANOVA) and Heckman's two-stage regression model to identify types of rationing faced by farmers and investigate factors that influence agricultural credit rationing by formal financial institutions. Data used in this study are gathered through a survey of 595 farmers in seven districts within Brong Ahafo Region of Ghana. Findings: – The result reveals that farmers face three types of rationing. Evidence from the Heckman two-stage models shows that engagement in off farm income generating activities, increase in farm size, positive balances on accounts and commercial orientation of the farmers has the potential to reduce rationing of credit applicants by formal lenders. Practical implications: – The results provide information on the factors that need to be considered as important in an attempt to reduce agricultural credit rationing by formal lenders. Originality/value: – The value of this study is that farmers would use the results of this study to improve access to required amount of agricultural credit from formal financial institutions. The information would also benefit stakeholders in the agricultural sector, particularly youth in agriculture program organized by Ministry of Food and Agriculture in Ghana as how to improve access to credit and reduce rationing of program participants by formal financial institutions.